Formation of the Russian Bank Deposit Insurance Scheme - Rykov, Sergey V. (International Journal of Economics and Financial Issues, 2016)
The paper presents the outcomes of research that reveals the main objective of formation of the Russian deposit insurance scheme (DIS) is protection of rights and legally protected interests of depositors in banks of the Russian Federation, confidence-building measures to the banking system and attraction of personal savings to banks. The paper has noted that over the last five years private deposits were one of the main sources of funding and growth of the Russian banking system. It was largely proved by the fact that the market of private deposits was the only competitive market of passives available to all banks. But now private deposits do not encourage growth of the Russian banking system. Considering the extent of protection, the Russian insurance scheme refers to the DIS that guarantees depositors limited coverage. The paper has also offered to compute premium accounts due to the deposit base risk adjustment. Keywords: deposit insurance, deposit risk, bank deposit-sourcing mechanism, JEL Classifications: G20, G21, E40